2011
DOI: 10.1177/0022002711400864
|View full text |Cite
|
Sign up to set email alerts
|

Political Institutions and Street Protests in Latin America

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(33 citation statements)
references
References 32 publications
(38 reference statements)
0
32
0
1
Order By: Relevance
“…Thus, partisans are constantly exposed to examples of political conflict that give them reason to feel that political processes in America are unsatisfactory. This is particularly problematic given the research demonstrating the link between dissatisfaction with government institutions and political violence (Dunning, 2011;Machado et al, 2011;Tsfati & Cohen, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, partisans are constantly exposed to examples of political conflict that give them reason to feel that political processes in America are unsatisfactory. This is particularly problematic given the research demonstrating the link between dissatisfaction with government institutions and political violence (Dunning, 2011;Machado et al, 2011;Tsfati & Cohen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These normative ideals encourage people to trust in the system and engage in traditional democratic behaviors (Tsfati & Cohen, 2005). When citizens perceive that democratic institutions are not functioning properly and/or their actions cannot affect government behavior, they are more likely to endorse alternative forms of engagement such as incivility, aggression, or even violence (Dunning, 2011;Machado, Scartascini, & Tommasi, 2011;Tsfati & Cohen, 2005).…”
Section: Political Efficacy and Support For Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Předně hypotézy o vlivu korupce je třeba testovat i u dalších států, zda zkušenost s korupcí vede k vyšší politické participaci jen u zemí, kde se úplatkářství vyskytuje, jak ostatně napovídají výsledky regresních modelů v případě Venezuely, anebo se projevuje i jinde. Zjišťovat, jestli za mobilizací v důsledku korupční zkušenosti je pocit křivdy, rozhořčení, které respondenta vedou k volebním urnám či manifestovat na náměstí (Machado, Scartascini, Tommasi 2011). Sledovat i jiné volební tendence respondenta, než pouze (ne)účast či hlas pro alternativní politický subjekt, ale např.…”
Section: Závěryunclassified
“…In contrast, Moseley and Moreno [6] found that socioeconomic variables were not as relevant as political interest and civic engagement when predicting protest behavior in Argentina and Bolivia. Others contend that, rather than individual variables, it is the perceived strength of political institutions that influences support for protest participation [11]. Such divergent findings urge for a comprehensive approach to understanding protest attitudes in the region.…”
Section: Protests and Public Opinion In Latin Americamentioning
confidence: 99%